User involvement in the ergonomic development of a medical instrument: a longitudinal case study. Issue 2 (2nd April 2016) - Tóvölgyi, Sarolta
Abstract : In this study the focus is on the continuous ergonomic-focused development of a medical instrument that is capable of performing blood group serological tests. Primarily, a medical device must be clinically effective and safe. At the same time it must also meet the needs of its users. This calls for consideration of numerous ergonomic aspects. The development process of the product line in question was supported by a longitudinal series of carefully designed focus groups. Altogether, the 23 focus groups conducted included 245 participants from 72 laboratories. The aim of the empirical research was to collect users' experiences, ideas and needs as inputs for the following phase of the product development process. During the mentioned focus group analyses, around 100 development proposals were conceived. Besides presenting more of the mentioned development proposals, the focus group analysis was shown as a proper methodology to involve end-users in the development and implementation of new technology or devices.